The Role of Organic Farming in Reducing Greenhouse Gas Emissions from Agriculture in the European Union - Claudiu George Bocean (Agronomy)
Agriculture remains a key source of greenhouse gas (GHG) emissions within the European Union, posing substantial obstacles to achieving climate objectives and fostering sustainable development. On this background, organic farming stands out as a viable alternative, offering significant potential for reducing emissions. This study explores the impact of expanding organic farming on GHG emissions in the EU agricultural sector. The empirical research examines the connection between organic farming practices and GHG emission levels using structural equation modeling, complemented by Holt and ARIMA forecasting models, to project future trends based on expected growth in organic farmland. The findings highlight a robust negative influence (p < 0.001), demonstrating that organic farming practices are associated with tangible reductions in emissions. Forecasting analyses further reinforce this, predicting considerable declines in GHG emissions (by almost 14 percent below the level of 2008) as organic farming continues to expand for over 23% of agricultural land by 2035, according to the projections in this research. These insights underscore the critical role of organic farming in advancing the EU’s climate ambitions. The study concludes that broader adoption of organic practices offers a practical and impactful pathway for building a more sustainable agricultural system while mitigating environmental harm across member states.